(untitled) (Al-Qalaa Journal, 2024)
The researcher of the current study aims to examine and prove the positive effects of employing literary materials in learning English listening and speaking skills. At the College of Arts and Science – Missalata at Elmergib University. English language students face many obstacles in listening and speaking. These problems hinder their improvement as they lack social and cultural knowledge and have inadequate vocabulary. They have difficulty pronouncing some words and using the correct grammatical structure. The study was conducted on 40 students from the English Language Department through the descriptive-analytical method. Based on the findings of the case study, literary works (novels, poems, dramas) have a significant impact on empowering students’ listening and speaking abilities. The study revealed that the targeted students are weak in listening and speaking because they did not have the opportunity to do actual oral and auditory practice through listening to pure English in its social and cultural context and by native speakers. Consequently, they lack the necessary vocabulary, correct pronunciation, and differentiating between accents and grammatical structures to communicate in English effectively. These factors contribute to students’ self-esteem issues, frustration, anxiety, and difficulty understanding unfamiliar words from context, which can be effectively resolved through the use of literary works.